Pemberdayaan dan Pemanfaatan Tanaman Obat Keluarga (TOGA) di Desa Lengkese Kabupaten Takalar - Rosdianah Rahim; Rusdianto; Ayu Andira; Hajar Aswad; Nandita Fahira Suci; Riski Fahirah; Din Nurul Rasidin; Lisani; Siti Marwa (PPM LP2M UIN Alauddin Makassar, 2023)
Family Medicinal Plants (TOGA) is a type of plant of choice which is very useful as medicine with easy maintenance and relatively low cost. So that TOGA is an alternative to family medicine by means of processing and production that is simple and safe because it rarely causes side effects, is easy to process and can be consumed for first aid in cases of minor illnesses such as fever, cough, or to help maintain stamina. The existence of TOGA is very easy to find around community housing that has a plot of land or on a plantation. However, there are still many people who are not aware that these plants can be used as medicinal plants. The service is carried out in Lengkese Village, Takalar Regency, where geographically the majority of the population earns crops and farms. In addition, this village has plants that can be grown into family medicinal plants. The method used to carry out this service includes observation and data collection as well as planting of family medicinal plants available in the village. The result is the availability of land or family medicinal plant plantations that can be managed and utilized by the local community.